Preceding crops and residue management practices on performance of mustard under zero-till semi-arid condition - Amgain, LP; Sharma, AR (Agronomy Journal of Nepal, 2013)
A field experiment was conducted in 2010/11 and 2011/12 at New Delhi to study the performance of zero-till rainfed mustard. The influence of preceding rainy season crops, viz. pearl millet, cluster bean and green gram; and residue management, viz. no residue, crop residue and Leucaena twigs mulching on this mustard crop was observed. Pooled analysis of mustard seed yield was significantly higher (+51%) in 2010/11 (1.80 t/ ha) than 2011/12 (1.19 t/ha) due to favourable weather condition in the first year. Further, Leucaena twigs mulching resulted higher seed yield of 2.17 t/ha in 2010/11 than 1.94 t/ha in 2011/12. Green gram as preceding crop resulted significantly higher mustard yield in 2010/11, while it was higher after cluster bean in 2011/12. Interaction between crop residue and preceding rainy season crops on growth parameters exerted significant variations, while yield attributes showed the mixed response. Cluster bean with Leucaena twigs led to higher yield of mustard, followed by green gram with crop residue. Economic analysis exhibited the highest net return of mustard grown after cluster bean with Leucaena twigs mulching. From the findings it is observed that growth indices, yield, and yield attributes and economics of mustard were influenced significantly by preceding crops and crop residue application. The effect of Leucaena twigs was found better in 2010/11, while both crop residues and Leucaena twigs mulching were equally effective in 2011/12. Cluster bean as preceding crop to mustard resulted higher yield and net returns, followed by green gram and cluster bean with crop residues. It was suggested that mustard after cluster bean with Leucaena twigs was a high yielding and profitable cropping system under zero-till semi-arid condition. It was concluded that growing mustard after cluster bean with Leucaena twigs mulching resulted increased yield and profitable cropping system for rainfed areas in zero-till semi arid condition of New Delhi. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 23-32 DOI: http://dx.doi.org/10.3126/ajn.v3i0.8983